2018
DOI: 10.1111/ans.14961
|View full text |Cite
|
Sign up to set email alerts
|

Strategy for discriminating cholesterol and premalignancy in polypoid lesions of the gallbladder: a single‐centre, retrospective cohort study

Abstract: Background: The present study aimed to assess the risk factors of cholesterol and premalignancy in polypoid lesions of the gallbladder (PLGs) and to establish an appropriate treatment strategy. Methods: Data from patients who underwent cholecystectomy at the First Affiliated Hospital, School of Medicine, Zhejiang University, between January 2011 and July 2017, were collected retrospectively. Results: A total of 1561 patients were included in the present study. The cohort comprised of 636 (40.7%) males and 925 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 25 publications
0
17
0
2
Order By: Relevance
“…Thus, identifying the risk factors for cholesterol polyp formation is important for prevention and individualized treatment. However, previous etiological studies investigating risk factors for gallbladder polyps formation failed to separate cholesterol polyps from other types, such as inflammatory polyps and adenomatous polyps [4,6,8]. In addition, false-positive results are inevitable in the diagnosis of cholesterol polyps by abdominal ultrasound, a diagnostic method widely used in previous studies [11,12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, identifying the risk factors for cholesterol polyp formation is important for prevention and individualized treatment. However, previous etiological studies investigating risk factors for gallbladder polyps formation failed to separate cholesterol polyps from other types, such as inflammatory polyps and adenomatous polyps [4,6,8]. In addition, false-positive results are inevitable in the diagnosis of cholesterol polyps by abdominal ultrasound, a diagnostic method widely used in previous studies [11,12].…”
Section: Discussionmentioning
confidence: 99%
“…Cholesterol polyps account for the majority of all GBP, ranging from 63.0%-92.0%; the remaining are non-cholesterol GBP, such as adenomatous polyps, inflammatory polyps, and adenocarcinoma [1][2][3][4]. Previous studies based on ultrasound have shown variable risk factors associated with GBP, including a higher body mass index (BMI), male sex, higher glucose, higher low-density lipoprotein (LDL), lower high-density lipoprotein (HDL), increased triglycerides (TG), and higher serum total cholesterol (TC) [2,[4][5][6][7][8]. Currently, no consensus as to treatment has been reached, and tailored, evidence-based treatment for cholesterol polyps is rare.…”
Section: Introductionmentioning
confidence: 99%
“…Polypoid lesions of the gallbladder (GBP) are defined as any raised lesion of the mucosal surface of the gallbladder. Recently, with the advancement in sonographic tools and increased health screening examinations, the incidence of GBP has increased gradually from 5 to 10% in adults [ 1 ] and GBPs are found in 0.6–4% of the cholecystectomy specimens worldwide [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Polypoid lesions of the gallbladder (GBP) are de ned as any raised lesion of the mucosal surface of the gallbladder. Recently, with the advancement in sonographic tools and increased health screening examinations, the incidence of GBP has increased gradually from 5% to 10% in adults [1] and GBPs are found in 0.6 -4% of the cholecystectomy specimens worldwide [2].…”
Section: Introductionmentioning
confidence: 99%